PHYTOCHEMICAL TEST OF SPRUCE ROOT ETHANOL EXTRACT - Purba, Eva Dewi Rosmawati (Universitas Negeri Medan, 2024)
Spruce root (Casuarinaceae) is known to be useful empirically used as a medicine for hemorrhoids. To determine Phytochemical activity of pine roots, it is necessary to conduct research on “Phytochemical activity of pine roots”.The experimental research with posttest only design. Research site was in the Microbiology and Pharmacognosy Laboratory of the Pharmacy Study Program and the Biology Laboratory of Bangka Belitung University. Research object of Sea spruce roots (Casuarinaceae equisetifolia) were taken in Bangka Botanical Garden in fresh. It then was made into extracts. Research procedures were Plant determination and identification (2) Preparation (3) Standardization of extracts (Casuarinaceae) (4) Phytochemical test. (5) TLC.The results are Phytochemical test showed that the results of the content contained in the spruce root are Alkaloid, Flavonoid, Triterpenoid, Anthraquinone and Tannin.